Penciptaan Produk Eksklusif Melalui Aplikasi Material dan Tekstur Pada Karya Fotograf - Irwandi Irwandi; Agni Saraswati; Erna Kusuma Dewi (LP2M ISBI Bandung, 2024)
This research is an effort to synthesize, explore and experiment to formulate photographic products of applied art by combining aspects of photographic art and aspects of painting. Concretely, through this research, digital photo printing will be carried out on paper and canvas media which in the next stage will be applied with painting materials and techniques to get an exclusive impression. The physical consumption of photography is now increasingly focused on meeting domestic and artistic needs. The results of observations show that the texture in the painting has its own visual strength, which is not found in photographic works. The main question of this research is how to select, digitally print photos on certain media, and apply materials and painting techniques to produce unique, exclusive, and characteristic photo works through the application of materials and painting techniques. The innovation resulting from this research is a working model to increase the value of photo prints in society by adding textural elements resulting from the touch of a hand. The creative method for creating works refers to Graham Wallas in The Art of Thoughts which consists of stages: preparation, incubation, illumination and verification. The product will be analyzed by using Otto Ocvirk’s theory in Art Fundamentals Theory and Practice. He discusses that texture gives the illusion of a touch effect so that the surface character looks real. It is found that applying resin to photos printed on paper has a positive impact and corresponds to the illusory effect to be achieved. Keywords: texture, photograph, exclusive product